The evaluation of premixed biogas/air explosion characteristics in a 20 L closed vessel - Nur Aqidah, Muhammad Harinder Khan (2019)
A gas explosion involving biogas is a severe phenomenon that results from the combustion of a premixed gas cloud. As of today, several explosion accidents involving biogas have been reported worldwide. Extensive and comprehensive studies have been done to investigate the factors contributing to the explosion (i.e. the fuel concentration, initial pressure and temperature, and carbon dioxide (CO2) dilution). However, these studies have only been done involving fuel/air mixtures other than biogas. Since biogas is composed of 50 to 70% methane (CH4), 30 to 50% CO2 and traces of other gases, it is highly combustible. Lacked in its fundamental combustion and explosion characteristics will lead to a higher potential of explosion hazard especially in industries. In this study, a gas explosion in a confined space is considered. An experimental approach using the 20 L closed spherical vessel is adopted to investigate the explosion characteristics of the premixed biogas/air mixtures. The factors (i.e. equivalence ratio (ER), CO2 concentration and initial pressure) contributed to the premixed biogas/air explosion characteristics (i.e. the explosion overpressure (Pex), maximum explosion overpressure (Pmax), the maximum rate of pressure rise ((dP/dt)max) and gas deflagration index (KG) was evaluated. From the results, it was found that the premixed biogas/air having 40% vol/vol CO2 was the most severe when exploded at a slightly rich concentration (ER = 1.2) with Pex, Pmax and (dP/dt)max of 8.50 bar, 9.08 bar and 120.00 bar/ms respectively. Besides, the evaluation of CO2 concentration in the premixed biogas/air mixture also showed that the mixture having 45% vol/vol CO2 at ER of 1.2 was found to be the least severe when exploded with Pex, Pmax and (dP/dt)max of 7.60 bar, 8.05 bar and 82.25 bar/ms respectively. This was due to the physical effect of CO2 and thermal-diffusive instability. Further, the premixed biogas/air mixture was also found to be the most severe when exploded at an initial pressure of 1.1 bar with Pex, Pmax and (dP/dt)max of 9.90 bar, 10.90 bar and 1922.50 bar/ms respectively. This was due to the fewer spaces between molecules, higher reaction rate as well as due to the role of thermal-diffusive instability. This study also shows that the premixed biogas/air mixture at ER ranging from 0.8 to 1.5 to fall into St-3 hazard class that was the most severe when exploded. Verification of the Pmax obtained from the experimental results was also conducted using the FLame ACcelaration Simulator (FLACs) software. Results showed that the Pmax was found to be within the ± 30% limit of discrepancy and is considered satisfactory. The compared Pmax from this study with published data from literature also shows a comparable trend. As a conclusion, it shows that the ER, CO2 concentration and the initial pressure of the premixed biogas/air mixture has a significant impact on its explosion characteristics, which can lead to a catastrophic explosion.